Indirect Education Exploring Indirectness in Teaching and Research - Saeverot, Herner (Theorizing Education, 2022)
Indirect Education discusses direct and indirect pedagogies and the complexities of these concepts within the field of education practice and research. It addresses the question of when it is most beneficial to be indirect with regard to teaching and educational research. The book offers an original approach to education in how it reasserts our right to a sense of ownership and agency in educational explorations. It argues that there should be space for indirect ways of teaching and communication when matters without clear answers and objectives enter the educational sphere. Bringing together a mix of empirical studies presented with a degree of storytelling, the book explores the literature of educational theory to make a novel and relatable argument for making space for indirectness in learning contexts. Putting forward a compelling case that is necessary for education in the difficult times that we are living in, the book will appeal to academics, researchers and students in the fields of educational theory, pedagogy, leadership studies and educational practice. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.